Pedagogy as Praxis: Education and training in initial professional education for Community Workers and Youth Workers - Bradley, Ciara; Devlin , Maurice; Brennan, Patricia; Tierney , Hilary; Reynolds Conlon , Saoirse; Crickley , Anastasia (The Journal of Practice Teaching and Learning, 2024)
This paper examines apraxis-focused pedagogical approach to professional formation in community work and youth work developed over four decades at the Department of Applied Social Studies, Maynooth University. The approach is rooted in collectivity, participation, and empowerment, and is based on Freirean and feminist analysis of social structures and embedded systemic discriminations including racism. It aims to develop critical praxis in students through an integrated curriculum grounded in theory and practice, a dialectic of classroom and fieldwork learning, interactive assessments, active student participation in their practice learning, mentoring from departmental staff and fieldwork supervisors. Taken together these elements model ‘pedagogy as praxis’.